The Smallest Anthropoids The Marmoset/Callimico Radiation - Ford, Susan M.; Porter, Leila M.; Davis, Lesa C. (Developments in Primatology: Progress and Prospects,, 2009)
The Smallest Anthropoids:The Marmoset/Callimico Radiation represents a comprehensive examination of the callimico/marmoset clade, including the smallest anthropoid primates on earth. It explores these diminutive primates from a variety of perspectives including: phylogeny; reproductive, social, and cognitive behavior; ranging behavior and locomotion; anatomy; and conservation. In the last twenty years, the number of taxa recognized in this group has increased from three genera and five species to five genera comprising at least 22 species. Additionally, our understanding of the evolutionary relationships among these taxa has undergone substantial revision, and all are now considered to be closely related to one another (including callimicos). This volume is the first to synthesize data on these newly recognized taxa. It features contributions from geneticists, anatomists, and behaviorists around the world, providing access to major findings of key international researchers whose work has not been easily available to English-speaking scholars. These contributors use field and lab data to test major hypotheses on behavior, evolution, cognition, and other issues. The Smallest Anthropoids:The Marmoset/Callimico Radiation is a timely forum that identifies future avenues of action necessary to more fully understand and protect this intriguing radiation of diminutive monkeys. It will be of value to field ecologists, conservation groups, individuals working with captive marmosets, natural resource managers in South America, and NGO's, as well as to primatologists and zoologists interested in social behavior, locomotion and biomechanics, morphology, reproductive behavior, and biology. Susan M. Ford is Associate Professor and Chair of the Department of Anthropology, and past Director of the Center for Systematic Biology, Southern Illinois University. Leila M. Porter is Associate Professor in the Department of Anthropology, Northern Illinois University. Lesa C. Davis is Associate Professor of the Department of Anthropology and Special Assistant to the President, Northeastern Illinois University, and Research Associate in the Field Museum of Natural History.